NILAI MORAL DALAM EHON GURI TO GURA NO KAISUIYOKU KARYA NAKAGAWA RIEKO - Murtini, Riyana Hari (Japanese Literature, 2013)
Picture story book by Nakagawa Rieko entitled Guri To Gura No Kaisuiyoku are a children humanities that told story about Guri and Gura adventure. That adventure was started when Guri and Gura playing in the beach. When they was playing, Guri and Gura found a bottle contains letter, map, and float that sended by Sea Monster. Sea Monster said to anyone who find that letter to go to sea tower. Guri and Gura decide to go to that sea tower. When they arrived at sea tower Guri and Gura help Sea Monster to pick up his pearl that fall into a hole. Finally, that pearl is back safe with Guri and Gura. Sea monster really happy and try to return Guri and Gura kindness. This research purpose is describing intrinsic element that build picture story book Guri To Gura No Kaisuiyoku such as theme, character and characteristic, plot, setting, point of view. language style, and message. Then, describe moral value that found in picture story book Guri To Gura No Kaisuiyoku by looking of characters attitude, act, and behavior. Keywords : Ehon, Picture story book, intrinsic element, moral value.